Study of Damage and Microplastic Release in Clear Aligners Under Cyclic Loads - Claudia Barile; Caterina Casavola; Claudia Cianci; Domenico Ciavarella; Giovanni Pappalettera; Carmine Pappalettere; Vimalathithan Paramsamy Kannan (Engineering Proceedings, 2025)
In this research work, the mechanical performance of a thermoformed clear dental aligner is studied. Its performance is evaluated under the cyclic compression test, which is designed to simulate the occlusal forces applied on the aligner during swallowing operations for its entire usage period. The mechanical results show that the aligner exhibit stable energy absorption and stiffness behaviour throughout its use period and thus can potentially be used for clinical applications. The microplastic released from the aligner due to the fatigue-like damage is analysed using optical microscopy. Most of the microplastics released have larger dimensions, which may be excreted from the gastrointestinal tracts and have less possibility to pass through the epithelium passively. Therefore, the use of aligner may not pose any cytotoxic health risks.